La scienza e la rete - Francesca, Di Donato (Strumenti per la didattica e la ricerca, 2009)
The advent and spread of Internet and the Web have radically transformed the modes of communication. This book considers a particular ambit of online communication, namely that of science. In the first place, the author reconstructs the circumstances that gave rise to the modern system of scientific communication, and the qualitative and quantitative tools for scientific evaluation. After this, the analysis concentrates on the history, philosophy and architecture of the Web from its inception through to the most recent developments of both a technical (Semantic Web) and a socio-cultural kind (Web 2.0). Finally an open and democratic model for scientific communication is projected and proposed, made possible through the use of transparent, accessible and distributed tools.